Preparation of Nanosized α-Al2O3 Particles Using a Microwave Pretreatment at Mild Temperature - Hyun Soo Kim; No-Kuk Park; Tae Jin Lee; Myeong-Heon Um; Misook Kang (Advances in Materials Science and Engineering)
This study investigated the effect of microwave pretreatment to reduce the growth temperature of α-Al2O3. The microwave pre-treating of the synthesized powders at 1,000∘C produced rhombohedral structured α-Al2O3 with high specific surface area and dispersion; however the structure accumulated among the particles was seen above 1,200∘C when the microwave did not pretreated.